Effect of Garlic (Allium sativum L.) and Bitter Melon (Momordica charantia L.) on Alloxan-Induced Toxicity - Sasnita, Natalia; Indahsari, Noer Kumala; Tjandra, Lusiani (Jurnal Biologi Tropis, 2026)
Alloxan is a diabetogenic substance that damages pancreatic β-cells through mechanisms involving oxidative stress. This study aimed to evaluate the effects of extracts derived from bitter melon and garlic (Momordica charantia L. and Allium sativum L.) in liver histology of rats given alloxan. An experimental laboratory approach with a post-test control group design was applied. The animals were allocated into seven groups: K- as the negative control, K+ as the positive control, P0 receiving glibenclamide, P1 and P2 treated with garlic extract (100 and 150 mg/kgBW), and P3 and P4 given bitter melon extract at similar dose levels. Following the intervention, liver histopathology was assessed. The findings indicated that alloxan administration led to greater hepatic tissue damage compared to the negative control group. The P3 and P4 groups had the highest histopathology values, which suggested more serious liver damage. These results imply that the given doses of bitter melon and garlic extracts may raise the metabolic burden in hepatic tissue and did not show hepatoprotective benefits in alloxan-induced rats.